Raising Botswana's Human Resource Profile to Facilitate Economic Diversification and Growth - World Bank (Washington, DC, 2015)
Botswanaapos;s economic growth has hinged on its abundant natural resources, particularly diamonds, which generate nearly half of its fiscal revenues. In terms of sustainable growth, this dependency on natural resources poses the biggest challenge for the country. To prepare Botswana for life after diamonds, the government developed a growth paradigm in its vision 2016 strategy document (Presidential Task Group 1997), which suggests that the development of new economy skills will play an extremely important role in the country s future. Botswana is aiming to develop new engines of growth, supplementing the diamond industry with manufacturing, financial, and transport services, and transforming the country s entrepreneurship sector into a buoyant, productive, and innovative private sector led by entrepreneurs with cutting-edge skills. A key ingredient of this strategy is the development of a holistic approach to skills development. Botswana has achieved high enrollment in basic education (90 percent in primary education) and the government continues to invest a high share of gross domestic GDP, almost 8 percent, in the education sector. In 2010 11, expenditures on education amounted to 25 percent of total government expenditures. Nevertheless, a skills constraint is repeatedly cited as a major challenge for businesses in the country. In 2010, the Enterprise Survey for Botswana reported that of the 10 major business constraints, the majority of firms in the country reported skills shortage as the key problem (World Bank, 2010a). The country also has high unemployment rates reported at approximately 17.8 percent and approximately 27 percent, when discouraged jobseekers are included (CSO, 2011). This note reviews the current landscape of the education sector in Botswana and attempts to identify key bottlenecks in the supply of relevant skills for economic diversification. Recommendations for preparing students who can be readily integrated into the labor market are then offered, using examples of best practices from successful case studies.